Pengaruh Penambahan Sukrosa pada Manisan Kulit Semangka - Ntau, Sri Wahyuni (Gorontalo Agriculture Technology Journal, 2018)
Skin watermelon is a waste of fruit watermelon that pemanfaatanya as food still low. this study aims to know how to take advantage of the skin watermelon be sweets and find out the influence the addition of sucrose in candied skin watermelon. benefits of this study can optimize waste skin watermelon in order to have the economic value of a high. this study using the method consists of two stages of the first stage of immersion skin watermelon by using the calcium hydroxide, the second phase of boiling skin watermelon using sucrose. engineering data processing using the design of randomized complete (RAL), which consists of three treatment and three replicates. Of the test results organoleptic treatment is bestÂ  treatment A1 with water content 44,4%, sugar levels 10,27% and vitamin C is 2,41%.Keywords : sucrose, watermelon, skin watermelon